(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This study conducts an analysis of socio-philosophical studies during the period of independence, examining the evolution, themes, and impact of philosophical inquiries on the social fabric. Against the backdrop of political upheavals, social transformations, and cultural shifts characterizing the era of independence, this analysis seeks to unravel the intricate interplay between philosophy and society. The research scrutinizes the diverse strands of socio-philosophical thought that emerged during this period, encompassing inquiries into identity, justice, equality, freedom, and the role of the individual within the societal framework. Through a comprehensive review of seminal works, the study identifies key philosophical trends that have shaped the discourse on social issues and influenced public discourse. Furthermore, the analysis explores the intersections between socio-philosophical studies and political movements, shedding light on how philosophical ideas have informed and been shaped by the struggles for independence, civil rights, and social justice. It delves into the ways in which philosophical thought has permeated societal structures, policies, and public consciousness, contributing to the formation of national identities and the establishment of ethical foundations. By examining the contributions of prominent socio-philosophical thinkers, this study aims to provide insights into the enduring impact of philosophical discourse on societal development. It seeks to elucidate the role of philosophical inquiry in addressing contemporary challenges, fostering cultural resilience, and envisioning paths toward a more just and equitable future.